Conclusions (Scottish Historical and Archaeological Internet Reports, 2003)
Resistivity survey has been successful in revealing key elements of the structure of the barrow including side revetment walls, a flat frontal façade and possible mortuary structures confirming that the monument has the same morphology as Dalladies. Rabbit burrowing and tree roots have had little effect on the integrity of the major structural elements (revetment and façade) though it has not been possible to assess the more subtle damage that might have occurred.